Effects of Transcranial Stimulation on Resistance Exercise in Mentally Fatigued Subjects. - Solon-Júnior, Luiz José Frota; de Lima-Junior, Dalton; Roelands, Bart; Boullosa, Daniel; Ferreira, Maria Elisa Caputo; Fortes, Leonardo De Sousa (International Journal of Sports Medicine, 2026)
The objective was to analyze the effect of anodic transcranial direct current stimulation over the the primary motor cortex (M1) on resistance exercise in mentally fatigued individuals. Thirty-five participants performed a Stroop task to induce mental fatigue until they reached 50 mm on the visual analogue scale under three different conditions in a randomized, double-blind, crossover experimental trial. The participants completed a resistance training session with six sets for muscle failure with fixed load (Vload=1 ms-1) after the Stroop task. During the resistance training session, performance parameters as the maximum number of repetitions, power output, and bar velocity were recorded with a linear encoder. Muscle activation (surface electromyography) and the rating of perceived exertion were also measured throughout the resistance training session. The maximum number of repetitions, mean power output, and mean velocity were higher under the anodic transcranial direct current stimulation condition when compared to the sham and control conditions (p <0.05). Meanwhile, the relative surface electromyographic activity of the vastus lateralis, and the rating of perceived exertion per set were lower under the anodic transcranial direct current stimulation condition when compared to sham and control conditions (p <0.05). This study suggest that anodic transcranial direct current stimulation-induced arousal over the left-M1 brain area thus improving the resistance exercise performances while reducing vastus lateralis surface electromyographic activity and rating of perceived exertion in mentally fatigued subjects.